Influence of Adherend Surface Roughness on the Adhesive Bond Strength - Ghumatkar,A. (2016)
Abstract Surface treatment of the adherends prior to adhesive bonding plays an important role in the enhancing of strength and durability of bonded joints. In this work, an investigation on effect of adherend surface roughness on adhesive bond strength was performed. Single strap joints with different adherends (mild steel and aluminium) bonded with an epoxy resin (Araldite(r) 2015) were tested. The adherend surface was treated by mechanical abrasion process using an emery paper. Contact angle measurement and SEM analysis to understand the wettability and the failure mechanism of the joints were performed. It was found that an optimum surface roughness exists for a maximum bonding strength and the roughness range depends on the adherend material. The joint strength changes are associated not only simply by the increased bonding area, surface texture or mechanical interlocking, but also by the chemical characteristics of the surface and the chemical bond between them.